Students’ and Lecturers’ Perceptions on The Implementation of Online Learning During Covid-19 Pandemic - Prastyo, Yanuar Dwi; Harahap, Alvita (Jurnal Kiprah, 2021)
The objective of this research is to explore students’ and lecturers’ perceptions on the implementation of online learning during the Covid-19 pandemic at the English Department of Universitas Bandar Lampung. This research was qualitative research and used questionnaires and interviews as its instruments of data collection. The results of the research showed that the students' and lecturers' perceptions are quite satisfied with the implementation of online learning during the Covid-19 pandemic at the English Department of Universitas Bandar Lampung. Students and lecturers have similar perceptions on flexibility indicators, including accessibility and time management. Therefore, there are also differences between the student's and lecturers' perceptions of effectiveness and problems. They also give some suggestions for students, suggestions for lecturers, and suggestions for the university so that the quality of online learning that is already good enough can be improved again so that some of the shortcomings can be minimized in the future.